2006
DOI: 10.1038/nature05179
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of off-target effects in Drosophila RNA interference screens

Abstract: RNA interference (RNAi) in both plants and animals is mediated by small RNAs of approximately 21-23 nucleotides in length for regulation of target gene expression at multiple levels through partial sequence complementarities. Combined with widespread genome sequencing, experimental use of RNAi has the potential to interrogate systematically all genes in a given organism with respect to a particular function. However, owing to a tolerance for mismatches and gaps in base-pairing with targets, small RNAs could ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
253
2
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(266 citation statements)
references
References 26 publications
7
253
2
4
Order By: Relevance
“…Overall, mismatched siRNAs are somewhat less efficient than the fully complementary siRNAs, but higher levels of the mismatched siRNAs can compensate for this reduced efficiency. These results contradict prior claims that siRNAs require at least 19 nts of pairing to induce sequence-specific gene silencing in vivo (5)(6)(7)(8).…”
Section: Resultscontrasting
confidence: 56%
“…Overall, mismatched siRNAs are somewhat less efficient than the fully complementary siRNAs, but higher levels of the mismatched siRNAs can compensate for this reduced efficiency. These results contradict prior claims that siRNAs require at least 19 nts of pairing to induce sequence-specific gene silencing in vivo (5)(6)(7)(8).…”
Section: Resultscontrasting
confidence: 56%
“…Although off-target effects in RNAi have become a concern, nautilus dsRNA has not been reported to have offtarget issues in genomic wide screens (see http://flyrnai.org), and the similarity between the genetic and RNAi data supports this interpretation (25,26).…”
Section: A Gal4-inducible Nau Rnai Transgene Phenocopies the Nau Armgfpmentioning
confidence: 50%
“…Confounding the effective use of genome-scale RNAi screens has been the inability to discriminate between siRNAs that induce off-targeting effects or otherwise grossly affect general cellular functions, from those that target genes-of-interest (12). Directly relevant to this study is the prevalence of false positives resulting from off-targeting observed in a similar screen performed in Drosophila to identify Wnt pathway components (12,13).…”
Section: A High-throughput Rnai Screen For Wnt Pathway Components Usingmentioning
confidence: 73%
“…Directly relevant to this study is the prevalence of false positives resulting from off-targeting observed in a similar screen performed in Drosophila to identify Wnt pathway components (12,13). To limit the influence of off-targeting in our screen, we retested 530 siRNAs of interest identified from the primary screen ( Fig.…”
Section: A High-throughput Rnai Screen For Wnt Pathway Components Usingmentioning
confidence: 99%